PENERAPAN PEER TEACHING DALAM UPAYA MENINGKATKAN HASIL BELAJAR PERMAINAN BULUTANGKIS SISWA KELAS XI IPS 1 SMAS LABSCHOOL UPI - Mohamad Oki Ridollah, - (2020)
The learning process that can improve student learning outcomes in every subject is needed, one of which is in the physical education learning. The formation of students' attitudes in physical education learning can be applied through peer teaching learning models that are applied in badminton learning. The purpose of this study was to determine the application of peer teaching learning models can improve learning outcomes of badminton in schools. The method used is a classroom action research method. The population in this study were SMAS Labschool High School students who participated in badminton learning. The sample in this study was 30 students. Simple random sampling technique. The research instrument used was an observation technique. To find out student learning outcomes seen from the observation assessment which consists of 4 indicators with a range of assessment scores 1,2,3 and 4. Then the basic score can be formulated as a reference for measuring student learning outcomes based on each indicator. This means that there are significant results with the application of peer teaching learning models in an effort to improve learning outcomes of badminton games. Keywords:Peer Teaching learning model, Badminton Game Learning Outcomes